Representasi Ibu dalam Novel Moga Bunda Disayang Allah Karya Tere Liye - Dara Aghnia Nur Fadhliah; Muhamad Adji; Mochammad Irfan Hidayatullah (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
Mother is a person full of love and affection. The image of a mother is also featured in popular literary works in the form of a novel with the title Moga Bunda Disayang Allah by Tere Liye. The figure of a loving mother is always associated with mothers who conceive, give birth and raise their children. However, mothers who are full of affection for their children can also be carried out by women who have not gone through the process of conceiving and giving birth. This shows that the role of women in society and culture has been shaped into a figure full of affection. The method used in this study is a descriptive qualitative method to describe the mother figure in the novel. The results of the study found that there were three mother figures, Bunda, ibu-ibu gendut and ibu khayalan as loving mothers who were classified as biological and non-biological mothers whose roles in the family were shaped by society and culture. In conclusion, biological or non-biological mothers are still mothers who love and are always there for their children.